Local production systems in Brazil: mapping, typology and policy suggestions - Wilson Suzigan; Jo\~ao Furtado; Renato Garcia; Sergio Sampaio (European Regional Science Association (ERSA), 2004)
This paper sets out to advance further in the development of a methodology for mapping, classifying and characterizing Local Production Systems (LPS) in Brazil. Such effort is justified not only for the importance these systems have been amassing for generating jobs and social welfare, economic growth, exports and technological development, but also for the attention they have received from several public organisms and private institutions, many times lacking adequate methodological criteria, resulting in dispersion of efforts and waste of both public and private resources. Therefore, the main goal of the paper is to provide evidence that allows rationalizing public policies administration criteria and private actions directed to LPS, offering suggestions for policies and actions differentiated according to categories or types of systems with distinct characteristics according to their relevance to local or regional development as well as their importance in the context of the sector in which they are inserted. Key words: Local production systems; industrial clusters; mapping, public policy. JEL Classification: R12; R58; O18.
Keywords: R12; R58; O18; 330; Local production systems; industrial clusters; mapping; public policy